A label-free amperometric immunosensor for the detection of carcinoembryonic antigen based on novel magnetic carbon and gold nanocomposites1. Issue 26 (22nd March 2015) - Li, Faying; Jiang, Liping; Han, Jian; Liu, Qing; Dong, Yunhui; Li, Yueyun; Wei, Qin
<x xml:space="preserve">Abstract</x> In this work, a novel label-free electrochemical immunosensor was developed for the quantitative detection of carcinoembryonic antigen (CEA).